EFFECT OF MANAGERIAL OWNERSHIP, DEBT COVENANT, POLITICAL COST AND GROWTH OPPORTUNITIES ON ACCOUNTING CONSERVATISM LEVELSd Growth Opportunities On Accounting Conservatism Levels - Nuraeni, Chusnul; Tama, Annafi Indra (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2019)
The purpose of this study was to determine the effect of managerial ownership, debt covenants, political costs and growth opportunities on the level of accounting conservatism, case studies on manufacturing companies listed on the Indonesia Stock Exchange 2011-2015. Testing this hypothesis uses multiple regression analysis. The regression coefficient test (T Test) in this study shows that the debt covenant and growth opportunities have a significant negative effect on the level of accounting conservatism, while the managerial ownership and political cost variables have no significant effect on the level of accounting conservatism. Suggestions for this study are to be able to expand the research sample so that the results can be generalized and can also be used to add or replace other variables that can affect accounting conservatism.